Probing the Active Site of Class 3 L-Asparaginase by Mutagenesis: Mutations of the Ser-Lys Tandems of ReAV - Kinga Pokrywka; Marta Grzechowiak; Joanna Sliwiak; Paulina Worsztynowicz; Joanna I. Loch; Milosz Ruszkowski; Miroslaw Gilski; Mariusz Jaskolski (Biomolecules, 2025)
The ReAV enzyme from Rhizobium etli, a representative of Class 3 L-asparaginases, is sequentially and structurally different from other known L-asparaginases. This distinctiveness makes ReAV a candidate for novel antileukemic therapies. ReAV is a homodimeric protein, with each subunit containing a highly specific zinc-binding site created by two cysteines, a lysine, and a water molecule. Two Ser-Lys tandems (Ser48-Lys51, Ser80-Lys263) are located in the close proximity of the metal binding site, with Ser48 hypothesized to be the catalytic nucleophile. To further investigate the catalytic process of ReAV, site-directed mutagenesis was employed to introduce alanine substitutions at residues from the Ser-Lys tandems and at Arg47, located near the Ser48-Lys51 tandem. These mutational studies, along with enzymatic assays and X-ray structure determinations, demonstrated that substitution of each of these highly conserved residues abolished the catalytic activity, confirming their essential role in enzyme mechanism.